2011
DOI: 10.1073/pnas.1107666108
|View full text |Cite
|
Sign up to set email alerts
|

WAVE regulatory complex activation by cooperating GTPases Arf and Rac1

Abstract: The WAVE regulatory complex (WRC) is a critical element in the control of actin polymerization at the eukaryotic cell membrane, but how WRC is activated remains uncertain. While Rho GTPase Rac1 can bind and activate WRC in vitro, this interaction is of low affinity, suggesting other factors may be important. By reconstituting WAVE-dependent actin assembly on membrane-coated beads in mammalian cell extracts, we found that Rac1 was not sufficient to engender bead motility, and we uncovered a key requirement for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
180
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(187 citation statements)
references
References 35 publications
7
180
0
Order By: Relevance
“…Here, we establish that Arf79F not only localises at the cell edge with the WRC component Sra1 but is also essential for lamellipodium formation. This builds on our recent demonstration that Arf1 directly recruits and activates mammalian WRC in vitro (Koronakis et al, 2011).…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Here, we establish that Arf79F not only localises at the cell edge with the WRC component Sra1 but is also essential for lamellipodium formation. This builds on our recent demonstration that Arf1 directly recruits and activates mammalian WRC in vitro (Koronakis et al, 2011).…”
Section: Resultsmentioning
confidence: 68%
“…We recently demonstrated that mammalian Arf1 directly binds the structural homologues Sra1 and Nap1 (Koronakis et al, 2011) and therefore wondered whether Arf79F drives lamellipodium formation by recruiting WRC to the plasma membrane. First, purified in vitro myristoylated Arf79F was anchored to silica beads coated in a phospholipid bilayer consisting of equal amounts of phosphatidylcholine and phosphatidylinositol (PC:PI).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations